2018
DOI: 10.3390/ijms19030755
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical Characteristics, In Vitro Degradation, Cytotoxicity, and Antibacterial Evaluation of Zn-4.0Ag Alloy as a Biodegradable Material

Abstract: Zn-based biodegradable metallic materials have been regarded as new potential biomaterials for use as biodegradable implants, mainly because of the ideal degradation rate compared with those of Mg-based alloys and Fe-based alloys. In this study, we developed and investigated a novel Zn-4 wt % Ag alloy as a potential biodegradable metal. A thermomechanical treatment was applied to refine the microstructure and, consequently, to improve the mechanical properties, compared to pure Zn. The yield strength (YS), ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 44 publications
11
54
0
Order By: Relevance
“…Research on other binary combinations have also been reported, including zinc-copper (Zn-Cu) [66,106], zinc-lithium (Zn-Li) [107,108], zinc-aluminium (Zn-Al) [74,96,109], zinc-silver (Zn-Ag) [110,111], and zinc-manganese (Zn-Mn) [112,113].…”
Section: Binary Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on other binary combinations have also been reported, including zinc-copper (Zn-Cu) [66,106], zinc-lithium (Zn-Li) [107,108], zinc-aluminium (Zn-Al) [74,96,109], zinc-silver (Zn-Ag) [110,111], and zinc-manganese (Zn-Mn) [112,113].…”
Section: Binary Alloysmentioning
confidence: 99%
“…Li et al [111], studying the cytocompatibility of Zn-4.0Ag with murine fibroblast cells (L929) and human primary osteosarcoma cell (Saos-2), noted that the addition of silver does not alter the biocompatibility of Zn. Moreover, Ag adds antibacterial qualities to biodegradable Zn against Streptococcus gordonii (S. gordonii).…”
Section: Influence Of Alloyingmentioning
confidence: 99%
“…However, the alloys do not show obvious toxicity to the important organs of heart, liver, and kidney even though the Ag content may have negative effect on the biocompatibility. Since Zn‐4Ag alloy was examined to have certain cytotoxicity for the concentrated (100%, 33.3%) extracts to the cells (Li et al, 2018). The tracking of the biological reactions of the animals to the implanted alloys is more reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Zn‐4Ag alloys degraded at the rate of 10.75 ± 0.16 μg cm −2 day −1 . The alloy showed cytotoxic effect with decreased viability and proliferation of L929 and Saos‐2 cells for the concentrated (100, 33.3%) extracts and non‐cytotoxic effect for the diluted (16.7, 10%) extracts of Zn‐4Ag alloys, respectively (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation